Case report: Mounded and refractory keratoses (MARK), a novel presentation of pemphigus vulgaris - Le, Stephanie T.; Toussi, Atrin M.; Nava, Jordan E.; Downing, Lauren A.; Fung, Maxwell A. (Frontiers in Medicine, 2023)
Pemphigus vulgaris (PV) is a rare immunobullous disease. Although it classically presents as generalized flaccid blisters affecting the skin and mucosae, atypical cases of PV can be diagnostically challenging. Herein, we report an underrecognized non-blistering manifestation of pemphigus vulgaris, which we call mounded and refractory keratoses (MARK). MARK presents as exuberant scaling plaques on the scalp, often in skin of color. When MARK features are present, pemphigus vulgaris is prone to misdiagnosis, clinically and histopathologically, leading to delays in appropriate treatment. Specifically, biopsies from these patients may resemble acantholytic dyskeratosis, resulting in initial misdiagnosis. Thus, recognizing this presentation may aid physicians in diagnosing and monitoring recurrence in pemphigus vulgaris.